Low-hardness quick-forming TPU (thermoplastic polyurethane) granules for injection molding and preparation method thereof
The TPU pellets for low-hardness quick-forming injection molding prepared through specific formulas and processes solve the problems of mechanical strength, wear resistance and hardness stability of existing low-hardness TPUs, and achieve better mechanical properties and weather resistance.
Patent Information
- Application Number
- CN202411565192.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
The existing thermoplastic polyurethane elastomers with low hardness have deviations in mechanical strength, wear resistance and aging resistance, and are prone to instability in hardness and plasticizer odor problems due to plasticizer exudation.
Using a low hardness quick-forming injection molding TPU pellet, which includes a specific proportion of aliphatic diisocyanate, aromatic diisocyanate, chain extender, solubilizing microcrystalline zone structure agent, polyol, catalyst and antioxidant, through Preparation of a combined process of twin screw extruder and fluidized bed dryer.
It realizes the low hardness ultra-soft characteristics of TPU pellets, and at the same time improves its mechanical strength, wear resistance, heat resistance, tear resistance and weather resistance, solving the problems of hardness instability and plasticizer odor .
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of low-hardness thermoplastic polyurethane synthesis, and in particular to a low-hardness TPU pellet for fast-molding injection molding and a preparation method thereof. Background Art
[0002] As a special elastic material, the properties of thermoplastic polyurethane elastomer TPU are between plastic and rubber. It has higher strength than rubber, better flexibility and cold resistance than plastic, and has broad application prospects. The special properties of thermoplastic polyurethane elastomer mainly lie in the fact that the molecular chain is a special soft and hard segment block copolymer structure. The molecular chain basically has no cross-linking structure, and its strength mainly depends on the covalent bond force of the molecular chain and the van der Waals force and hydrogen bond between the macromolecular chains. Compared with other thermoplastic elastomer materials, TPU has a hardness range of 45A to 80D, and has comprehensive advantages in wear resistance, elasticity, mechanical properties, etc.
[0003] The hardness and mechanical properties of TPU mainly depend on the molecular chain structure of the soft segment and hard segment in the macromolecular chain, the ratio of soft segment to hard segment (R value), the molecular chain structure polarity and crystallinity (ability to form hydrogen bonds) of the soft segment and hard segment. The hard segment limits the mobility of the molecular chain in the macromolecular chain. The greater the hard segment content, the weaker the molecular chain mobility. It preferentially gathers together to form an ordered hard segment phase for regular arrangement. The ordered hard segment phase will separate from the soft segment to form a microphase separation, that is, a microcrystalline area. The microcrystalline area acts as a cross-linking point of the material. The more microcrystalline areas there are, the better the hardness, wear resistance and mechanical strength of the TPU. Low-hardness ultra-soft TPU has excellent softness and elasticity, and is widely used in hoses, sheaths, seals and other fields.
[0004] At present, the low-hardness thermoplastic polyurethane elastomer of 55-65A is obtained by combining the thermoplastic polyurethane elastomer of 65-75A hardness with an appropriate amount of plasticizer. Affected by the preparation process of existing industrial thermoplastic polyurethane elastomers, the hardness of conventional low-hardness thermoplastic polyurethane elastomers is 65-75A (without plasticizer), and the industrialization of thermoplastic polyurethane elastomers with lower hardness is limited. The main reason is that although the addition of small molecule plasticizers can reduce the hardness of TPU, there are often disadvantages such as plasticizer exudation, post-hardening and odor problems, which are not conducive to the development and application of low-hardness thermoplastic polyurethane elastomers. In addition, low-hardness thermoplastic polyurethane elastomers also have the following common problems: deviations in mechanical strength, wear resistance, and aging resistance, which limit the development of low-hardness thermoplastic polyurethane elastomers. To this end, the inventor provides a low-hardness TPU pellet for fast-molding injection molding and a preparation method thereof. Summary of the invention
[0005] In order to solve the problems of mechanical strength, wear resistance and aging resistance of the existing low-hardness thermoplastic polyurethane elastomer in the above-mentioned prior art, such as the deviation of plasticizer leakage leading to unstable hardness and plasticizer odor caused by subsequent hardening of TPU, the present invention provides a low-hardness TPU pellet for fast-forming injection molding and a preparation method thereof.
[0006] The invention provides a TPU pellet with low hardness and fast forming for injection molding, which is realized by the following technical scheme: A low-hardness fast-molding TPU pellet for injection molding has a Shore hardness of 58-65A, an R value of 22-30wt%, a tensile strength ≥20MPa, a tensile fracture rate ≥1000%, a tear strength ≥40 kN / m, and a wear resistance <50g / cm 2 .
[0007] A low-hardness fast-molding TPU pellet for injection molding comprises the following raw materials in parts by weight: 8-12 parts of aliphatic diisocyanate, 14-20 parts of aromatic diisocyanate, 4-8 parts of chain extender, 0.05-0.5 parts of solubilizing microcrystalline domain structuring agent, 68-72 parts of polyol, 0.00005-0.001 parts of catalyst, and 0.5-1 parts of antioxidant.
[0008] The chain extender is composed of at least one of 2,2-dihydroxymethylpropionic acid, 2,2-dihydroxymethylbutyric acid, and N,N-dihydroxyethylglycine and at least one of diol, diamine, and monoalcohol amine with a molecular weight of 60-500 g / mol.
[0009] The preparation method of the solubilizing microcrystalline region structuring agent is as follows: surface activated carbon nanotubes are placed in a methacryloxysilane aqueous solution for ultrasonic dispersion treatment for 5-10 minutes, then reduced pressure filtration and vacuum drying are performed, the obtained surface grafted methacryloxy carbon nanotubes are dispersed in an organic solvent to obtain a carbon nanotube dispersion, hydroxy acrylate and an azo initiator are added to react at medium and low temperature for 5-30 minutes, reduced pressure filtration, multiple washings, vacuum drying, and ball milling to obtain a solubilizing microcrystalline region structuring agent; the hydroxy acrylate is at least one of di(hydroxyethyl) phosphate, 11-undecyl phosphonate, and rosin acid glycerol ester. The hydroxyl group contained in the solubilizing microcrystalline region structuring agent of the present application reacts with the carboxyl group contained in at least one of 2,2-dihydroxymethylpropionic acid, 2,2-dihydroxymethylbutyric acid, and N,N-dihydroxyethylglycine in the chain extender to produce an ester bond, and the solubilizing microcrystalline region structuring agent is connected to the TPU main chain as a side chain. The solubilizing microcrystalline region structuring agent serves as a physical cross-linking point, and the controllable design of the number of microcrystalline regions of the TPU as a whole can effectively improve the mechanical strength, wear resistance, heat resistance, and tear strength of the TPU as a whole. The phosphate group and ester bond can play a plasticizing role, so adding an appropriate amount of the solubilizing microcrystalline region structuring agent does not affect the hardness, and a 58-65A low-hardness ultra-soft TPU pellet can be obtained. The pellet has relatively excellent mechanical strength, wear resistance, heat resistance, tear strength, and weather resistance, filling the gap in domestic low-hardness and high-performance TPU.
[0010] Preferably, the preparation method of the solubilizing microcrystalline domain structuring agent is as follows: S1. Place 0.5-2 parts of surface activated carbon nanotubes in 0.5-1L of a methacryloxysilane aqueous solution, wherein the surface activated carbon nanotubes are one or more of hydroxylated single-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, amino single-walled carbon nanotubes, and amino multi-walled carbon nanotubes, wherein the methacryloxysilane aqueous solution contains 0.05-0.5wt% methacryloxysilane, and the methacryloxysilane is at least one of KH 570 and KH 571, heat in a water bath to 40-45°C, perform ultrasonic dispersion treatment for 5-10 minutes, filter under reduced pressure, and dry under vacuum to obtain functional carbon nanotubes; S2. Disperse 0.5-2 parts of the functional carbon nanotubes with methacryloyloxy groups grafted on the surface of S1 in 200-500 mL of a toluene / DMF mixed solvent to obtain a carbon nanotube dispersion, and dropwise add a hydroxyacrylate / azo initiator mixture into the carbon nanotube dispersion, wherein the hydroxyacrylate is di(hydroxyethyl) phosphate, the azo initiator is azobisisobutyronitrile, the amount of the hydroxyacrylate / azo initiator mixture added is 0.01-0.2 times the mass of the functional carbon nanotubes, the mass ratio of hydroxyacrylate to azo initiator in the hydroxyacrylate / azo initiator mixture is 199:1, the dropping speed of the hydroxyacrylate / azo initiator mixture is 2-3 drops / min, heat in a water bath to 50-65°C, perform polymerization reaction for 10-15 minutes, cool to room temperature in an ice bath, perform reduced pressure filtration, rinse multiple times, vacuum dry, and ball mill to obtain a solubilizing microcrystalline domain framework agent.
[0011] The preparation method of the solubilizing microcrystalline domain structuring agent in the present invention is relatively simple, which is convenient for realizing batch production and reducing the overall cost.
[0012] Preferably, the aliphatic diisocyanate is at least one of isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hexamethylene-1,6-diisocyanate, and 2,2,4-trimethylhexamethylene diisocyanate; and the aromatic diisocyanate is at least one of MDI, MDI-50, and carbodiimide-modified MDI.
[0013] Preferably, the aliphatic diisocyanate is isophorone diisocyanate or 2,2,4-trimethylhexamethylene diisocyanate; the aromatic diisocyanate is MDI-50; and the mass ratio of isophorone diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate to aromatic diisocyanate MDI-50 in the aliphatic diisocyanate is (0.5-1):(1-2):(7-8).
[0014] By adopting the above technical scheme, the crystallinity of aliphatic diisocyanate is lower than that of aromatic diisocyanate. By doping a proper amount of aliphatic diisocyanate segment structure into the TPU molecular segment, the overall hardness of TPU can be reduced while improving the overall anti-yellowing performance, and the addition of a proper amount of aromatic diisocyanate is ensured without affecting the rapid prototyping processing performance of the overall production process.
[0015] Preferably, the catalyst is at least one of dibutyltin dilaurate, bismuth isooctanoate, and stannous octoate; the antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, and antioxidant 168.
[0016] Preferably, the diol in the chain extender is at least one of 1,5-pentanediol, 1,6-hexanediol, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, neopentyl glycol, diethylene glycol, and 3-methyl-1,5-pentanediol; the diamine in the chain extender is at least one of ethylenediamine, 1,6-hexanediamine, 1,4-butanediamine, and methylcyclohexanediamine; and the monoalcoholamine in the chain extender is ethanolamine and / or diglycolamine.
[0017] Preferably, the polyol is at least two of polyester diols, polyether diols, and polycarbonate diols with a number average molecular weight of 800 to 3500; the polyester diol is poly (1,5-pentanediol-3-methyl adipate), poly (1,5-pentanediol-3-methyl sebacic acid), poly (1,4-cyclohexanedicarboxylic acid-3-methyl 1,5-pentanediol), semi-crystalline dimer acid polyester polyol PLOS-ZY2100, low crystalline linear polyester polyol The polyether diol is at least one of polytetramethylene glycol PLOS-ZY1200 and low crystalline dimer acid polyester polyol PLOS-ZY2250; the polyether diol is at least one of polytetramethylene glycol PTMEG, branched polytetramethylene glycol PTG-L, and branched polytetramethylene glycol PTXG; the polycarbonate diol includes at least one of polycaprolactone hexamethylene carbonate diol and polycarbonate 3-methyl 1,5-pentanediol-1,6-hexanediol ester diol.
[0018] Preferably, the polyol is composed of polyester diol, polyether diol and polycarbonate diol with a number average molecular weight of 103 to 3*103 in a molar ratio of (20-40):(50-65):(5-20); the polyether diol is branched polytetrahydrofuran diol PTG-L-1000 and PTG-L-2000; the polycarbonate diol is polycaprolactone hexamethylene carbonate diol with a number average molecular weight of 103 to 2*103.
[0019] Preferably, the polyester diol is composed of poly 1,5-pentanediol-3-methyl sebacic acid ester diol and semi-crystalline dimer acid polyester polyol PLOS-ZY2100; or the polyester diol is composed of poly 1,5-pentanediol-3-methyl adipate diol and low-crystalline dimer acid polyester polyol PLOS-ZY2250; or the polyester diol is composed of poly 1,4-cyclohexanedicarboxylic acid-1,5-pentanediol-3-methyl ester diol and low-crystalline linear polyester polyol PLOS-ZY1200.
[0020] By adopting the above technical solution, it can be ensured that the prepared TPU pellets have a relatively lower hardness at the same R value, and the prepared TPU pellets have relatively better mechanical strength, hydrolysis resistance, wear resistance and transparency.
[0021] The preparation method of TPU pellets for low hardness fast molding injection molding provided in this application is achieved by the following scheme: A method for preparing TPU pellets for low-hardness fast-molding injection molding comprises the following steps: Step 1, aliphatic diisocyanate, part of polyol, part of catalyst and part of antioxidant are uniformly mixed, and reacted at 90-95° C. for 80-120 min to obtain -NCO terminated polyurethane prepolymer A; The ratio of the molar amount of -NCO in the aliphatic diisocyanate to the molar amount of -OH in the polyol in the polyurethane prepolymer A is (1.05-1.5):1; the catalyst content in the polyurethane prepolymer A is 500-600ppm of the aliphatic diisocyanate; the added amount of the antioxidant in the polyurethane prepolymer A is 20-30wt% of the total weight of the antioxidant; Meanwhile, part of aromatic diisocyanate, part of polyol, part of catalyst and part of antioxidant are uniformly mixed, and reacted at 70-80° C. for 40-60 min to obtain -NCO terminated polyurethane prepolymer B; The aromatic diisocyanate in the polyurethane prepolymer B is 40-60wt% of the total mass of the aromatic diisocyanate; the ratio of the molar amount of -NCO in the aromatic diisocyanate polyol to the molar amount of -OH in the polyol in the polyurethane prepolymer B is (1.05-1.5):1; the catalyst content in the polyurethane prepolymer B is 150-300ppm of the aliphatic diisocyanate; the added amount of the antioxidant in the polyurethane prepolymer B is 30-40wt% of the total mass of the antioxidant; Step 2, adding the polyurethane prepolymer A in step 1 to the first trough of the twin-screw extruder; adding the polyurethane prepolymer B in step 1 to the second trough of the twin-screw extruder; stirring the accurately measured solubilizing microcrystalline region framework agent and the chain extender to obtain the mixture, and then stirring the remaining aromatic diisocyanate, chain extender, polyol, catalyst, and antioxidant at 60-65°C for 3-5 minutes to mix evenly, and then adding it to the third trough of the twin-screw extruder; the temperature of the first trough is 70-75°C, the temperature of the second trough is 60-65°C, the temperature of the third trough is 70-80°C, the extrusion temperature range of the twin-screw extruder is 160-220°C, and the twin-screw extruder is divided into twelve temperature zones, the setting temperature of the first temperature zone is 100-110°C, and the setting temperature of the second temperature zone is 200-300°C. The temperature is 120-125°C, the third temperature zone is set at 130-140°C, the fourth temperature zone is set at 150-160°C, the fifth temperature zone is set at 165-170°C, the sixth temperature zone is set at 180-185°C, the seventh temperature zone is set at 195-200°C, the eighth temperature zone is set at 195-200°C, the ninth temperature zone is set at 195-200°C, the tenth temperature zone is set at 180-185°C, the eleventh temperature zone is set at 160-165°C, the twelfth temperature zone is set at 145-150°C, the screw speed is 20-40rpm, the head temperature is 140-160°C, the screw aspect ratio is (40-48): 1, and a gear pump is used to discharge the material from the twin-screw extruder; Step three, the molten extrudate discharged from the twin-screw extruder in step two is water-cooled, granulated, and dried to obtain a semi-finished product, the semi-finished product is placed in a fluidized bed dryer, the temperature is adjusted to 80-85°C and dried for 8-12 minutes until the water content is less than 0.03%, and the obtained pellets are transferred to a 78-80°C oven for 20-24 hours of heat adjustment to obtain low-hardness fast-molding TPU pellets for injection molding.
[0022] The preparation method of the low-hardness fast-forming TPU pellets for injection molding provided in the present application has low difficulty in industrial production and manufacturing, is convenient for planning and mass production of low-hardness fast-forming TPU pellets for injection molding, reduces the overall production cost, is convenient for market promotion and popularization, and fills the gap of low-hardness and high-performance TPU in China.
[0023] In summary, this application has the following advantages: 1. The TPU pellets prepared by the present invention have a hardness of 58-65A, and have excellent mechanical strength, wear resistance, heat resistance, tear strength, and weather resistance. The application range is wider, and it fills the gap of low hardness and high performance TPU in China.
[0024] 2. In the present invention, the polyol composition is optimized and designed to ensure that the prepared TPU pellets have a relatively lower hardness at the same R value, and the prepared TPU pellets have relatively better mechanical strength, hydrolysis resistance, wear resistance, and transparency, thereby improving the market competitiveness of the prepared TPU pellets and being customizable to meet the needs of different application fields. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples. Example
[0026] A low-hardness fast-molding TPU pellet for injection molding comprises the following raw materials in parts by weight: 8-12 parts of aliphatic diisocyanate, 14-20 parts of aromatic diisocyanate, 4-8 parts of chain extender, 0.05-0.5 parts of solubilizing microcrystalline domain structuring agent, 68-72 parts of polyol, 0.00005-0.001 parts of catalyst, and 0.5-1 parts of antioxidant.
[0027] The R value of low-hardness fast-molding TPU pellets for injection molding is 22-30wt%, the Shore hardness is 58-65A, the tensile strength is ≥20MPa, the tensile fracture rate is ≥1000%, the tear strength is ≥40 kN / m, and the wear resistance is <50g / cm 2 .
[0028] The chain extender is composed of at least one of 2,2-dihydroxymethylpropionic acid, 2,2-dihydroxymethylbutyric acid and N,N-dihydroxyethylglycine and at least one of diol, diamine and monoalcohol amine with a molecular weight of 60-500 g / mol.
[0029] The diol in the chain extender is at least one of 1,5-pentanediol, 1,6-hexanediol, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, neopentyl glycol, diethylene glycol, and 3-methyl-1,5-pentanediol.
[0030] The diamine in the chain extender is at least one of ethylenediamine, 1,6-hexanediamine, 1,4-butanediamine and methylcyclohexanediamine.
[0031] The monoalcoholamine in the chain extender is ethanolamine and / or diglycolamine.
[0032] Preferably, the chain extender is composed of 2,2-dimethylolpropionic acid, 1,5-pentanediol and 1,6-hexanediol.
[0033] The aliphatic diisocyanate is at least one of isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hexamethylene-1,6-diisocyanate, and 2,2,4-trimethylhexamethylene diisocyanate.
[0034] Preferably, the aliphatic diisocyanate is isophorone diisocyanate or 2,2,4-trimethylhexamethylene diisocyanate.
[0035] The aromatic diisocyanate is at least one of MDI, MDI-50, and carbodiimide-modified MDI.
[0036] Preferably, the aromatic diisocyanate is MDI-50.
[0037] Preferably, the mass ratio of isophorone diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate and aromatic diisocyanate MDI-50 in the aliphatic diisocyanate is (0.5-1):(1-2):(7-8). The advantages of the above diisocyanate formula design are as follows: the crystallinity of aliphatic diisocyanates is lower than that of aromatic diisocyanates, and the TPU molecular chain segment is doped with a proper amount of aliphatic diisocyanate chain segment structure, which can reduce the overall hardness of TPU and improve the overall anti-yellowing performance, and ensure that the appropriate amount of aromatic diisocyanate is added without affecting the rapid prototyping processing performance of the overall production process.
[0038] The catalyst is at least one of dibutyltin dilaurate, bismuth isooctanoate and stannous octoate.
[0039] Preferably, the catalyst is dibutyltin dilaurate.
[0040] The antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, and antioxidant 168. Preferably, the antioxidant is antioxidant 1010 or antioxidant 168.
[0041] The polyol is at least two of polyester diol, polyether diol and polycarbonate diol with a number average molecular weight of 800 to 3500. Preferably, the polyol is at least two of polyester diol, polyether diol and polycarbonate diol with a number average molecular weight of 10 3 ~3*10 3 The polyester diol, polyether diol and polycarbonate diol are composed in a molar ratio of (20-40):(50-65):(5-20).
[0042] The polyester diol is at least one of poly(3-methyl 1,5-pentanediol adipate), poly(3-methyl 1,5-pentanediol sebacate), poly(3-methyl 1,5-pentanediol 1,4-cyclohexanedicarboxylate), semi-crystalline dimer acid polyester polyol PLOS-ZY2100, low crystalline linear polyester polyol PLOS-ZY1200, and low crystalline dimer acid polyester polyol PLOS-ZY2250.
[0043] Preferably, the polyester diol is composed of poly (3-methyl 1,5-pentanediol sebacate) diol and semi-crystalline dimer acid polyester polyol PLOS-ZY2100 in a mass ratio of (1-5):(1-5).
[0044] Preferably, the polyester diol is composed of poly(3-methyl-1,5-pentanediol adipate) diol and low-crystalline dimer acid polyester polyol PLOS-ZY2250 in a mass ratio of (1-5):(1-5).
[0045] Preferably, the polyester diol is composed of poly (1,4-cyclohexanedicarboxylic acid-3-methyl-1,5-pentanediol) ester diol and low-crystalline linear polyester polyol PLOS-ZY1200 in a mass ratio of (1-5):(1-5).
[0046] The polyether diol is at least one of polytetrahydrofuran diol PTMEG, branched polytetrahydrofuran diol PTG-L, and branched polytetrahydrofuran diol PTXG. Preferably, the polyether diol is branched polytetrahydrofuran diol PTG-L-1000 and PTG-L-2000.
[0047] The preparation of the solubilizing microcrystalline domain structuring agent is as follows: S1.1, placing 0.5-2 parts of surface activated carbon nanotubes in 0.5-1L of methacryloxysilane aqueous solution, wherein the surface activated carbon nanotubes are one or more of hydroxylated single-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, amino single-walled carbon nanotubes, and amino multi-walled carbon nanotubes, the methacryloxysilane content in the methacryloxysilane aqueous solution is 0.05-0.5wt%, and the methacryloxysilane is at least one of KH 570 and KH 571, heating in a water bath to 40-45°C, performing ultrasonic dispersion treatment for 5-10 minutes, filtering under reduced pressure, and vacuum drying to obtain functional carbon nanotubes; S1.2, dispersing 0.5-2 parts of the functional carbon nanotubes with methacryloyloxy groups grafted on the surface in S1 in 200-500 mL of a toluene / DMF mixed solvent to obtain a carbon nanotube dispersion, and dripping a hydroxy acrylate / azo initiator mixture into the carbon nanotube dispersion, wherein the hydroxy acrylate is at least one of di(hydroxyethyl) phosphate, 11-undecyl phosphonate, and rosin acid glycerol ester, the azo initiator is azobisisobutyronitrile, and the hydroxy acrylate / azo initiator mixture is added dropwise. The amount of the nitrogen initiator mixture added is 0.01-0.2 times the mass of the functional carbon nanotubes, the mass ratio of hydroxy acrylate to azo initiator in the hydroxy acrylate / azo initiator mixture is 199:1, the dripping speed of the hydroxy acrylate / azo initiator mixture is 2-3 drops / min, the water bath is heated to 50-65° C., the polymerization reaction is 10-15 minutes, and after cooling to room temperature in an ice bath, the mixture is filtered under reduced pressure, rinsed multiple times, vacuum dried, and ball milled to obtain a solubilized microcrystalline region framework agent.
[0048] It should be noted that the content of surface activated carbon nanotube activation groups (recommended to be less than 1wt%) and the content of methacryloxysilane affect the surface density of methacryloxy groups grafted on the surface of functional carbon nanotubes. Excessive surface density of methacryloxy groups will lead to an increase in the cross-linking density between the TPU molecular chains finally formed, and the movement of the molecular chains will be too restricted, which is not conducive to the control of the hardness of TPU. In addition, when the double bonds in hydroxy acrylate and the double bonds of methacryloyloxy grafted on the surface of functional carbon nanotubes are polymerized, it is necessary to control the addition amount of hydroxy acrylate / azo initiator mixture and functional carbon nanotubes, the solid content of carbon nanotube dispersion is low, the hydroxy acrylate content is less than 0.2 times of the functional carbon nanotubes, and the polymerization temperature should not be too high. It is recommended to react at 50-65°C for 10-15 minutes. If the reaction time is too long and the system viscosity is too high, it is not conducive to filtering and washing the residual by-products on the surface - self-polymers, but also affects the subsequent ball milling efficiency, increases the difficulty of ball milling, and is not conducive to mass production. It can effectively reduce the probability of self-polymerization of double bonds in methacryloyloxy on the surface of functional carbon nanotubes and double bonds in hydroxy acrylate, and improve the probability of obtaining the target solubilizing microcrystalline region structuring agent, that is, improve the yield of the solubilizing microcrystalline region structuring agent.
[0049] The polycarbonate diol includes polycarbonate caprolactone hexamethylene diol and / or polycarbonate 3-methyl 1,5 pentanediol-1,6-hexanediol ester diol. Preferably, the polycarbonate diol has a number average molecular weight of 10 3 ~2*10 3 Poly(hexamethylene carbonate) caprolactone glycol.
[0050] In the present invention, a combination optimization experiment is conducted on the types and amounts of polyester diols, polyether diols and polycarbonate diols to ensure that the prepared TPU pellets have a relatively lower hardness at the same R value, and have relatively better mechanical strength, hydrolysis resistance, wear resistance and transparency, thereby improving the market competitiveness of the prepared TPU pellets. By adjusting the types and amounts of polyester diols, polyether diols and polycarbonate diols, they can be customized to meet the needs of different application fields.
[0051] A method for preparing TPU pellets for low-hardness fast-molding injection molding comprises the following steps: Step 1, aliphatic diisocyanate, part of polyol, part of catalyst, and part of antioxidant are uniformly mixed, the ratio of the molar amount of -NCO in the aliphatic diisocyanate to the molar amount of -OH in the polyol in the polyurethane prepolymer A is (1.05-1.5):1; the catalyst content in the polyurethane prepolymer A is 500-600ppm of the aliphatic diisocyanate; the amount of antioxidant added in the polyurethane prepolymer A is 20-30wt% of the total weight of the antioxidant, and the reaction is carried out at 90-95°C for 80-120min to obtain -NCO-terminated polyurethane prepolymer A; At the same time, part of the aromatic diisocyanate, part of the polyol, part of the catalyst, and part of the antioxidant are uniformly mixed, wherein the aromatic diisocyanate in the polyurethane prepolymer B is 40-60wt% of the total mass of the aromatic diisocyanate; the ratio of the molar amount of -NCO in the aromatic diisocyanate polyol to the molar amount of -OH in the polyol in the polyurethane prepolymer B is (1.05-1.5):1; the catalyst content in the polyurethane prepolymer B is 150-300ppm of the aliphatic diisocyanate; the amount of the antioxidant added in the polyurethane prepolymer B is 30-40wt% of the total mass of the antioxidant; and the reaction is carried out at 70-80°C for 40-60min to obtain the -NCO-terminated polyurethane prepolymer B; At the same time, the solubilizing microcrystalline region structuring agent is prepared; Step 2, adding polyurethane prepolymer A into the first trough of a twin-screw extruder, wherein the temperature of the first trough is 70-75° C.; Add the polyurethane prepolymer B in step 1 into the second trough of the twin-screw extruder, and the temperature of the third trough is 60-65°C; Preliminarily react the accurately measured solubilizing microcrystalline domain framework agent with at least one of 2,2-dihydroxymethylpropionic acid, 2,2-dihydroxymethylbutyric acid and N,N-dihydroxyethylglycine in the chain extender at 50-65° C. for 15-30 min under the catalysis of tetrabutyl titanate, and then stir the obtained mixture with the remaining aromatic diisocyanate, chain extender, polyol, catalyst and antioxidant at 60-65° C. for 3-5 min to mix evenly, and add the obtained mixture to the third trough of the twin-screw extruder, and the temperature of the third trough is 70-80° C.; the extrusion temperature range of the twin-screw extruder is 120-200° C., the screw speed is 20-40 rpm, the head temperature is 140-160° C., and the screw aspect ratio is (40-48):1, and the material is discharged from the twin-screw extruder using a gear pump; Preferably, the twin-screw extruder is divided into twelve temperature zones, the first temperature zone is set at 100-110°C, the second temperature zone is set at 120-125°C, the third temperature zone is set at 130-140°C, the fourth temperature zone is set at 150-160°C, the fifth temperature zone is set at 165-170°C, the sixth temperature zone is set at 180-185°C, the seventh temperature zone is set at 195-200°C, the eighth temperature zone is set at 195-200°C, the ninth temperature zone is set at 195-200°C, the tenth temperature zone is set at 180-185°C, the eleventh temperature zone is set at 160-165°C, and the twelfth temperature zone is set at 145-150°C; Step three, the molten extrudate discharged from the twin-screw extruder in step two is water-cooled, granulated, and dried to obtain a semi-finished product, the semi-finished product is placed in a fluidized bed dryer, the temperature is adjusted to 80-85°C and dried for 8-12 minutes until the water content is less than 0.03%, and the obtained pellets are transferred to a 78-80°C oven for 20-24 hours of heat adjustment to obtain low-hardness fast-molding TPU pellets for injection molding.
[0052] The preparation scheme of the solubilizing microcrystalline region structuring agent ①, the specific method is as follows: S1.1, 1g of surface hydroxyl activated carbon nanotubes (industrial grade multi-walled carbon nanotubes TNIMH4 from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, -OH content 0.76wt%, OD: 30-80nm, length <10microns, SSA> 60m 2 / g) was placed in 1L KH 570 aqueous solution (KH 570 content was 0.05 wt%) and stirred at 200 rpm for 3 min, then heated in a water bath to 40-45°C for 10 min of ultrasonic dispersion treatment (40kHz / 800W), filtered under reduced pressure, and dried in vacuum to obtain functional carbon nanotubes; S1.2. Disperse 1 g of functional carbon nanotubes with methacryloyloxy groups grafted on the surface in S1 in 500 mL of toluene / DMF mixed solvent (toluene / DMF volume ratio = 2:1), stir at 200 rpm for 5 min to obtain a carbon nanotube dispersion, and add 0.4 g of a mixture of di(hydroxyethyl) phosphate / azobisisobutyronitrile (the mass ratio of di(hydroxyethyl) phosphate to azobisisobutyronitrile is 199:1) to the carbon nanotube dispersion at a rate of 2 drops / min. After the addition is completed, heat to 60°C in a water bath, react for 10 min, cool to room temperature in an ice bath, filter under reduced pressure, and dry in vacuo. Place the solid material in a planetary ball mill for ball milling using zirconium oxide beads as grinding balls and mill at a speed of 320 rpm for 15 min to obtain a solubilizing microcrystalline domain structuring agent.
[0053] The difference between the preparation scheme ② of the solubilizing microcrystalline region structuring agent and the preparation scheme ① of the solubilizing microcrystalline region structuring agent is: S1.2, 1g of the functional carbon nanotubes with methacryloyloxy grafted on the surface in S1 is dispersed in 500mL of toluene / DMF mixed solvent (toluene / DMF volume ratio = 2:1), stirred at 200rpm for 5min to obtain a carbon nanotube dispersion, and 0.4g of a 11-undecylphosphonate / azobisisobutyronitrile mixed solution (the mass ratio of 11-undecylphosphonate to azobisisobutyronitrile is 199:1) is added to the carbon nanotube dispersion at a rate of 2 drops / min, after the addition is completed, the water bath is heated to 60°C, the polymerization reaction is carried out for 10min, the temperature is cooled to room temperature in an ice bath, and the solid material is filtered under reduced pressure and dried in vacuo, and then ball milled in a planetary ball mill with zirconium oxide beads as grinding balls and a ball milling speed of 320rpm for 15min to obtain a solubilizing microcrystalline region structuring agent.
[0054] The difference between the preparation scheme ③ of the solubilizing microcrystalline region structuring agent and the preparation scheme ① of the solubilizing microcrystalline region structuring agent is as follows: S1.2, 1g of the functional carbon nanotubes with methacryloyloxy groups grafted on the surface in S1 is dispersed in 500mL of a toluene / DMF mixed solvent (toluene / DMF volume ratio = 2:1), stirred at 200rpm for 5min to obtain a carbon nanotube dispersion, and 0.4g of di(hydroxyethyl) phosphate / 11-phosphonic acid undecane is added to the carbon nanotube dispersion at a rate of 2 drops / min. A mixture of acrylate / azobisisobutyronitrile (phosphoric acid di(hydroxyethyl) ester, 11-phosphonic acid undecyl acrylate, azobisisobutyronitrile in a mass ratio of 199:199:2) was prepared. After the addition was completed, the mixture was heated to 60°C in a water bath, and the polymerization reaction was carried out for 10 minutes. After the mixture was cooled to room temperature in an ice bath, it was filtered under reduced pressure and dried in a vacuum. The solid material was placed in a planetary ball mill for ball milling. Zirconia beads were used as the grinding balls. The ball milling speed was 320 rpm and the ball milling was carried out for 15 minutes to obtain a solubilizing microcrystalline domain structuring agent.
[0055] Example 1: A low-hardness fast-molding TPU pellet for injection molding is prepared from 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 3 g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9 g of dibutyltin dilaurate, 27 g of antioxidant 1010, and 3 g of antioxidant 168.
[0056] A method for preparing TPU pellets for low-hardness fast-molding injection molding comprises the following steps: Step 1: 333.44 g of isophorone diisocyanate, 800 g of poly(3-methyl 1,5-pentanediol adipate) (Japan Kuraray P-2010), 1400 g of polytetrahydrofuran diol PTMEG (BASF PoiyTHF 2000), 0.15 g of dibutyltin dilaurate, 8.1 g of antioxidant 1010, and 0.9 g of antioxidant 168 were mixed evenly, and the mixture was heated to 94±0.5° C. and reacted for 100 min to obtain -NCO-terminated aliphatic polyurethane prepolymer A; Meanwhile, 200.2 g of MDI-50, 600 g of poly(1,5-pentanediol-3-methyl adipate) (Kuraray P-2010, Japan), 600 g of poly(tetrahydrofuran diol) PTMEG (PoiyTHF 2000, BASF), 0.07 g of dibutyltin dilaurate, 8.1 g of antioxidant 1010, and 0.9 g of antioxidant 168 were mixed evenly, and reacted at 75±0.5° C. for 60 min to obtain -NCO-terminated aromatic polyurethane prepolymer B; Step 2, adding polyurethane prepolymer A into the first trough of a twin-screw extruder, the temperature of the first trough being 75° C.; Add the polyurethane prepolymer B in step 1 into the second trough of the twin-screw extruder, and the temperature of the third trough is 60°C; 3 g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 241.4 g of 2,2-dihydroxymethylpropionic acid, and 0.05 g of tetrabutyl titanate were mixed uniformly, and then heated to 60° C. for pre-reaction for 30 min to obtain a mixture. The obtained mixture was then stirred at 60° C. for 5 min with 675.7 g of MDI-50, 118.2 g of 3-methyl-1,5-pentanediol, 1000 g of polytetrahydrofuran diol PTMEG, 0.68 g of dibutyltin dilaurate, 10.8 g of antioxidant 1010, and 1.2 g of antioxidant 168 for uniform mixing at 60° C. The obtained mixture was added to the third trough of the twin-screw extruder, and the trough temperature of the third trough was 75° C. The extrusion temperature range in the twin-screw extruder was 120- 200℃, the twin-screw extruder is divided into twelve temperature zones, the set temperature of the first temperature zone is 110℃, the set temperature of the second temperature zone is 125℃, the set temperature of the third temperature zone is 140℃, the set temperature of the fourth temperature zone is 155℃, the set temperature of the fifth temperature zone is 170℃, the set temperature of the sixth temperature zone is 185℃, the set temperature of the seventh temperature zone is 195℃, the set temperature of the eighth temperature zone is 200℃, the set temperature of the ninth temperature zone is 200℃, the set temperature of the tenth temperature zone is 185℃, the set temperature of the eleventh temperature zone is 165℃, the set temperature of the twelfth temperature zone is 150℃, the screw speed is 36rpm, the head temperature is 160℃, the screw length-diameter ratio is 45:1, and a gear pump is used to discharge the material from the twin-screw extruder; Step three, the molten extrudate discharged from the twin-screw extruder in step two is water-cooled, granulated, and dried to obtain a semi-finished product, the semi-finished product is placed in a fluidized bed dryer, the temperature is adjusted to 80°C and dried for 12 minutes until the water content is less than 0.03%, and the obtained pellets are transferred to an 80°C oven for 24 hours of heat adjustment to obtain low-hardness fast-molding TPU pellets for injection molding.
[0057] The R value of the obtained TPU pellets is 26.3wt%, the Shore hardness (ASTM D 2240) is 60A, the tensile strength (GB1040-79) is 23.8MPa, the tensile break rate (GB1040-79) is 1048%, the tear strength (GB / T 529-2008) is 44.1kN / m, and the wear resistance is 42.6g / cm 2 .
[0058] The difference between Example 2 and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 15g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0059] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 26.5MPa, the tensile break rate (GB1040-79) is 975%, the tear strength (GB / T 529-2008) is 48.1kN / m, and the wear resistance is 35.6g / cm 2 .
[0060] The difference between Example 3 and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 30g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0061] The Shore hardness of TPU pellets (ASTM D 2240) is 61A, the tensile strength (GB1040-79) is 30.3MPa, the tensile break rate (GB1040-79) is 915%, the tear strength (GB / T 529-2008) is 53.7kN / m, and the wear resistance is 32.8g / cm 2 .
[0062] The difference between Example 4 and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 15g of the solubilizing microcrystalline domain structuring agent in Preparation Example 2, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0063] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 26.8MPa, the tensile break rate (GB1040-79) is 969%, the tear strength (GB / T 529-2008) is 48.5kN / m, and the wear resistance is 35.1g / cm 2 .
[0064] The difference between Example 5 and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 15g of the solubilizing microcrystalline domain structuring agent in Preparation Example 3, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0065] The Shore hardness of TPU pellets (ASTM D 2240) is 61A, the tensile strength (GB1040-79) is 24.2MPa, the tensile break rate (GB1040-79) is 951%, the tear strength (GB / T 529-2008) is 48.7kN / m, and the wear resistance is 34.9g / cm 2 .
[0066] The difference between Example 6 and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(3-methyl 1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 3 g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9 g of dibutyltin dilaurate, 27 g of antioxidant 1010, and 3 g of antioxidant 168.
[0067] The difference in the preparation method of TPU pellets for low hardness fast molding injection molding is: Step 1: 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 800 g of poly(3-methyl 1,5-pentanediol adipate) (Japan Kuraray P-2010), 1400 g of poly(tetrahydrofuran diol) PTMEG (BASF PoiyTHF 2000), 0.15 g of dibutyltin dilaurate, 8.1 g of antioxidant 1010, and 0.9 g of antioxidant 168 were mixed evenly, and the mixture was heated to 94±0.5° C. and reacted for 100 min to obtain -NCO-terminated aliphatic polyurethane prepolymer A.
[0068] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 24.3MPa, the tensile break rate (GB1040-79) is 971%, the tear strength (GB / T 529-2008) is 45.6kN / m, and the wear resistance is 41.8g / cm 2 .
[0069] By comparing Example 6 with Example 1, it can be seen that the aliphatic diisocyanate composed of isophorone diisocyanate IPDI and 2,2,4-trimethylhexane diisocyanate TMDI as the hard segment block has better mechanical properties and wear resistance than isophorone diisocyanate IPDI alone as the hard segment block when the hardness of the two is the same.
[0070] The difference between the raw materials for preparing the TPU pellets in the control experiment scheme A of Example 1 and Example 1 is that the solubilizing microcrystalline domain structuring agent is not contained. The difference between the preparation method of the TPU pellets for low hardness fast molding injection molding is: Step 2, adding polyurethane prepolymer A into the first trough of a twin-screw extruder, the temperature of the first trough being 75° C.; Add the polyurethane prepolymer B in step 1 into the second trough of the twin-screw extruder, and the temperature of the third trough is 60°C; 675.7 g of MDI-50, 241.4 g of 2,2-dihydroxymethylpropionic acid, 118.2 g of 3-methyl-1,5-pentanediol, 1000 g of polytetrahydrofuran diol PTMEG, 0.68 g of 118.2 g of 3-methyl-1,5-pentanediol, 10.8 g of antioxidant 1010, and 1.2 g of antioxidant 168 were stirred at 60°C for 5 min to mix evenly, and the resulting mixture was added to the third trough of the twin-screw extruder, and the temperature of the third trough was 75°C; the extrusion temperature range in the twin-screw extruder was 120-200°C, and the twin-screw extruder was divided into twelve temperature zones, and the first temperature zone was set to The temperature is 110°C, the second temperature zone is set to 125°C, the third temperature zone is set to 140°C, the fourth temperature zone is set to 155°C, the fifth temperature zone is set to 170°C, the sixth temperature zone is set to 185°C, the seventh temperature zone is set to 195°C, the eighth temperature zone is set to 200°C, the ninth temperature zone is set to 200°C, the tenth temperature zone is set to 185°C, the eleventh temperature zone is set to 165°C, the twelfth temperature zone is set to 150°C, the screw speed is 36rpm, the head temperature is 160°C, the screw aspect ratio is 45:1, and a gear pump is used to discharge the material from the twin-screw extruder.
[0071] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 18.9MPa, the tensile break rate (GB1040-79) is 1076%, the tear strength (GB / T 529-2008) is 41.1kN / m, and the wear resistance is 51.2g / cm 2 .
[0072] By comparing Example 1 with the control experiment scheme A, it can be seen that when the solubilizing microcrystalline region structuring agent is added in an amount of 0.05-0.06wt%, the hardness of the TPU prepared in Example 1 with the solubilizing microcrystalline region structuring agent is maintained at 60A, and the tensile properties, tear strength and wear resistance are uniformly and significantly improved.
[0073] The difference between control experiment scheme B and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 3 g of hydroxylated multi-walled carbon nanotubes, 0.9 g of dibutyltin dilaurate, 27 g of antioxidant 1010, and 3 g of antioxidant 168.
[0074] The difference in the preparation method of TPU pellets for low hardness fast molding injection molding is: Step 2, adding polyurethane prepolymer A into the first trough of a twin-screw extruder, the temperature of the first trough being 75° C.; Add the polyurethane prepolymer B in step 1 into the second trough of the twin-screw extruder, and the temperature of the third trough is 60°C; 675.7 g of MDI-50, 241.4 g of 2,2-dihydroxymethylpropionic acid, 118.2 g of 3-methyl-1,5-pentanediol, 30 g of hydroxylated multi-walled carbon nanotubes, 1000 g of polytetrahydrofuran diol PTMEG, 0.68 g of 118.2 g of 3-methyl-1,5-pentanediol, 10.8 g of antioxidant 1010, and 1.2 g of antioxidant 168 were stirred at 60° C. for 5 min and mixed evenly. The resulting mixture was added to the third trough of the twin-screw extruder, and the temperature of the third trough was 75° C. The extrusion temperature range in the twin-screw extruder was 120-200° C., and the twin-screw extruder was divided into twelve temperature zones. The set temperature of the first temperature zone is 110℃, the set temperature of the second temperature zone is 125℃, the set temperature of the third temperature zone is 140℃, the set temperature of the fourth temperature zone is 155℃, the set temperature of the fifth temperature zone is 170℃, the set temperature of the sixth temperature zone is 185℃, the set temperature of the seventh temperature zone is 195℃, the set temperature of the eighth temperature zone is 200℃, the set temperature of the ninth temperature zone is 200℃, the set temperature of the tenth temperature zone is 185℃, the set temperature of the eleventh temperature zone is 165℃, the set temperature of the twelfth temperature zone is 150℃, the screw speed is 36rpm, the head temperature is 160℃, the screw aspect ratio is 45:1, and a gear pump is used to discharge the material from the twin-screw extruder.
[0075] The Shore hardness of TPU pellets (ASTM D 2240) is 66A, the tensile strength (GB1040-79) is 32.7MPa, the tensile break rate (GB1040-79) is 835%, the tear strength (GB / T 529-2008) is 55.4kN / m, and the wear resistance is 30.5g / cm 2 .
[0076] By comparing Example 3 with Control Experimental Scheme B, it can be seen that when the addition amount of hydroxylated multi-walled carbon nanotubes is 0.5-0.6wt%, the hardness of the TPU prepared in Control Experimental Scheme B increases from 60A to 66A. The hydroxylation contained on the surface of the multi-walled carbon nanotubes participates in the polyurethane synthesis reaction, improves the crosslinking degree between the TPU molecular chains, and relatively greatly improves the overall tensile properties, tear strength, and wear resistance. However, the hydroxylated multi-walled carbon nanotubes have a significant improvement on the hardness, which does not meet the requirements of the present invention.
[0077] The difference between control experiment scheme C and Example 1 is that the low hardness fast molding TPU pellets for injection molding are composed of 333.44g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 241.4g of 2,2-dimethylolpropionic acid, 1400g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 1g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168. The Shore hardness (ASTM D 2240) of the TPU pellets is 60A, the tensile strength (GB1040-79) is 19.8MPa, the tensile fracture rate (GB1040-79) is 1087%, the tear strength (GB / T 529-2008) is 42.3kN / m, and the wear resistance is 47.2g / cm 2 .
[0078] The difference between control experiment scheme D and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 333.44 g of isophorone diisocyanate IPDI (Covestro Desmodur I isophorone diisocyanate, containing a mixture of 75% cis and 25% trans isomers), 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylolpropionic acid, 1400 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 3000 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 35g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168. The Shore hardness (ASTM D 2240) of the TPU pellets is 62A, the tensile strength (GB1040-79) is 34.6MPa, the tensile fracture rate (GB1040-79) is 846%, the tear strength (GB / T 529-2008) is 54.9kN / m, and the wear resistance is 31.7g / cm 2 .
[0079] From the added amount of solubilizing microcrystalline domain structuring agent in Example 1 and Control Experimental Scheme C, based on the above formulation, 0.05 wt% of the solubilizing microcrystalline domain structuring agent has begun to have a weak effect on the hardness of TPU, that is, the critical lower limit threshold.
[0080] From the added amount of solubilizing microcrystalline domain structuring agent in Example 3 and Control Experimental Scheme D, based on the above formulation, 0.5 wt% of the solubilizing microcrystalline domain structuring agent has begun to have a strong impact on the hardness of TPU, i.e., the critical upper limit threshold.
[0081] Comparison of Examples 1-3 with control experiments CD shows that the appropriate content of the solubilizing microcrystalline region structuring agent is 0.05-0.5 wt %.
[0082] The difference between control experiment scheme E and example 1 is that a low hardness fast molding TPU pellet for injection molding is made of 1251.1g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 234.7g of 2,2-dihydroxymethylpropionic acid, 1500g of poly (1,5-pentanediol adipate-3-methyl adipate) (Japan Kuraray P-2010), 3000g of polytetrahydrofuran diol PTMEG (BASF PoiyTHF 2000), 3g of the solubilizing microcrystalline domain structuring agent in preparation example 1, 0.80g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0083] A method for preparing TPU pellets for low-hardness fast-molding injection molding comprises the following steps: Step 1: 625.65 g of isophorone diisocyanate, 1500 g of poly(3-methyl 1,5-pentanediol adipate) (Japan Kuraray P-2010), 2000 g of polytetrahydrofuran diol PTMEG (BASF PoiyTHF 2000), 0.3 g of dibutyltin dilaurate, 13.5 g of antioxidant 1010, and 1.5 g of antioxidant 168 were mixed evenly, and the mixture was heated to 75±0.5° C. and reacted for 100 min to obtain an -NCO-terminated polyurethane prepolymer; Step 2, adding the polyurethane prepolymer into the first trough of the twin-screw extruder, the temperature of the first trough is 75° C.; 3 g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 234.7 g of 2,2-dihydroxymethyl propionic acid, and 0.05 g of tetrabutyl titanate were mixed evenly, and the mixture was pre-reacted at 60° C. for 30 min to obtain a mixture, and the mixture was added to the second trough of the twin-screw extruder. The temperature of the third trough was 60° C.; 625.5 g of MDI-50, 118.2 g of 3-methyl-1,5-pentanediol, 1000 g of polytetrahydrofuran diol PTMEG, 0.5 g of dibutyltin dilaurate, 13.5 g of antioxidant 1010, and 1.5 g of antioxidant 168 were stirred at 60 ° C for 5 min to mix evenly, and the resulting mixture was added to the third trough of the twin-screw extruder, and the temperature of the third trough was 75 ° C; the extrusion temperature range of the twin-screw extruder was 120-200 ° C, and the twin-screw extruder was divided into twelve temperature zones, the first temperature zone was set at 110 ° C, and the second temperature zone was set at 110 ° C. The temperature of the third temperature zone is 125°C, the temperature of the third temperature zone is 140°C, the temperature of the fourth temperature zone is 155°C, the temperature of the fifth temperature zone is 170°C, the temperature of the sixth temperature zone is 185°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 200°C, the temperature of the ninth temperature zone is 200°C, the temperature of the tenth temperature zone is 185°C, the temperature of the eleventh temperature zone is 165°C, the temperature of the twelfth temperature zone is 150°C, the screw speed is 36rpm, the head temperature is 160°C, the screw aspect ratio is 45:1, and a gear pump is used to discharge the material from the twin-screw extruder; Step three, the molten extrudate discharged from the twin-screw extruder in step two is water-cooled, granulated, and dried to obtain a semi-finished product, the semi-finished product is placed in a fluidized bed dryer, the temperature is adjusted to 80°C and dried for 12 minutes until the water content is less than 0.03%, and the obtained pellets are transferred to an 80°C oven for 24 hours of heat adjustment to obtain low-hardness fast-molding TPU pellets for injection molding.
[0084] The Shore hardness of TPU pellets (ASTM D 2240) is 66A, the tensile strength (GB1040-79) is 27.5MPa, the tensile break rate (GB1040-79) is 825%, the tear strength (GB / T 529-2008) is 48.1kN / m, and the wear resistance is 39.4g / cm 2 .
[0085] Comparison of Example 1 with Control Experimental Scheme E shows that the hardness of TPU prepared by isophorone diisocyanate IPDI and MDI-50 in a molar ratio of 3:7 is relatively low at about 60A, while the hardness of TPU prepared by pure MDI-50 is relatively low at about 66A, and the tensile strength, tear strength and wear resistance are increased, but the tensile fracture performance is significantly reduced. The benzene ring structure in MDI-50 reduces the flexibility of the TPU molecular chain and increases the rigidity. Therefore, the aliphatic diisocyanate and the aromatic diisocyanate in a molar ratio of 3:7 form a diisocyanate composition, which improves the hardness and anti-yellowing performance of TPU while ensuring tensile strength, tear strength and wear resistance, and has a stronger competitive advantage and application range.
[0086] The current German BASF S60A12P low hardness TPU has a Shore hardness of 60A, a tensile strength of 35.5MPa, a tensile break rate (GB1040-79) of 756%, a tear strength (GB / T 529-2008) of 45.5kN / m, and abrasion resistance of 34g / cm 2 .
[0087] In summary, the low hardness TPU pellets prepared by the present invention can be comparable to the comprehensive performance of BASF S60A12P, filling the gap of low hardness and high performance TPU in China.
[0088] In order to further explore the influence of polyols in the soft segment on the hardness of the finished TPU and its tensile properties, wear resistance and tear resistance, the present invention limits the TPU formula design R value to 26.2-26.4%, and further designs and studies different polyol combinations in the formula to explore the influence on the hardness, tensile properties, wear resistance and tear resistance of the prepared TPU.
[0089] The difference between Example 7 and Example 6 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 Desmodur 2460M, 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylol propionic acid, 1320 g of poly(3-methyl 1,5-pentanediol adipate) (Japan Kuraray P-2010), 2860 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 220g of polycaprolactone hexamethylene glycol CD2220PL (Dacelide Co., Ltd., Japan), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0090] The Shore hardness of TPU pellets (ASTM D 2240) is 61A, the tensile strength (GB1040-79) is 25.1MPa, the tensile break rate (GB1040-79) is 1019%, the tear strength (GB / T 529-2008) is 46.9kN / m, and the wear resistance is 40.5g / cm 2 .
[0091] The difference between Example 8 and Example 6 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylol propionic acid, 1760 g of poly(1,5-pentanediol adipate) (Japan Kuraray P-2010), 2200 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 440g of polycaprolactone hexamethylene glycol CD2220PL (Dacelide Co., Ltd., Japan), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0092] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 25.5MPa, the tensile break rate (GB1040-79) is 1041%, the tear strength (GB / T 529-2008) is 47.4kN / m, and the wear resistance is 39.7g / cm 2 .
[0093] The difference between Example 9 and Example 6 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylol propionic acid, 880 g of poly(1,5-pentanediol-3-methyl adipate) (Japan Kuraray P-2010), 2640 g of polytetramethylene glycol PTMEG (BASF PoiyTHF 2000), 880g of polycaprolactone hexamethylene glycol CD2220PL (Dacelide Co., Ltd., Japan), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0094] The Shore hardness of TPU pellets (ASTM D 2240) is 61A, the tensile strength (GB1040-79) is 26.0MPa, the tensile break rate (GB1040-79) is 947%, the tear strength (GB / T 529-2008) is 48.1kN / m, and the wear resistance is 39.1g / cm 2 .
[0095] It can be seen from Examples 6 and 7-9 that the hardness of the synthesized TPU is maintained at 60A, and it has relatively excellent mechanical properties and wear resistance.
[0096] Example 10 is a control scheme between Examples 1 and 6, in that: a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2 g of 3-methyl-1,5-pentanediol, 241.4 g of 2,2-dimethylol propionic acid, 1460 g of poly (1,5-pentanediol adipate-3-methyl) (Japan Kuraray P-2010), 1480 g of poly (tetramethylene glycol) PTMEG (BASF PoiyTHF 2000), 146g of polycaprolactone hexamethylene glycol CD2220PL (Dacelide Co., Ltd., Japan), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0097] The Shore hardness of TPU pellets (ASTM D 2240) is 61A, the tensile strength (GB1040-79) is 26.4MPa, the tensile break rate (GB1040-79) is 876%, the tear strength (GB / T 529-2008) is 48.6kN / m, and the wear resistance is 38.7g / cm 2 .
[0098] By comparing Example 10 with Examples 6-9, it can be seen that the polyester diol, polyether diol and polycarbonate diol are compounded in a molar ratio of (20-40):(50-65):(5-20) to form a polyol combination, and the prepared TPU has better comprehensive performance and lower production cost.
[0099] The difference between Example 11 and Example 1 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 241.4g of 2,2-dihydroxymethylpropionic acid, 1760g of poly(3-methyl-1,5-pentanediol adipate) (Japan Kuraray P-2010), 2200g of branched polytetramethylene glycol PTG-L-2000 (Japan Hotoko Chemical Industry Co., Ltd.), 440g of poly(caprolactone hexamethylene carbonate) CD2220PL (Japan Daicel Corporation), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0100] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 25.8MPa, the tensile break rate (GB1040-79) is 981%, the tear strength (GB / T 529-2008) is 48.2kN / m, and the wear resistance is 39.5g / cm 2 .
[0101] The difference between Example 12 and Example 11 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 253.5g of 2,2-dihydroxymethylpropionic acid, 1936g of low-crystalline linear polyester polyol PLOS-ZY1200, 2020g of branched polytetramethylene glycol PTG-L-2000 (Japan Hotoko Chemical Industry Co., Ltd.), 440g of polycaprolactone hexamethylene glycol CD2220PL (Japan Daicel Corporation), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0102] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 24.9MPa, the tensile break rate (GB1040-79) is 1047%, the tear strength (GB / T 529-2008) is 47.4kN / m, and the wear resistance is 40.5g / cm 2 .
[0103] The difference between Example 13 and Example 11 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 241.4g of 2,2-dihydroxymethylpropionic acid, 1320g of polysebate-3-methyl-1,5-pentanediol ester diol (self-made by Zhejiang Hexin Technology Co., Ltd., molecular weight 3000), 484g of semi-crystalline dimer acid polyester polyol PLOS-ZY2100, 2200g of branched polytetrahydrofuran diol PTG-L-2000 (Japan Baotugu Chemical Industry Co., Ltd.), 440g of polycaprolactone hexamethylene carbonate diol CD2220PL (Japan Daicel Corporation), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0104] The preparation method of poly(3-methyl-1,5-pentanediol sebacic acid) ester is as follows: sebacic acid and 3-methyl-1,5-pentanediol are put into a reactor at a molar ratio of 2:2.1, and then tetraisopropyl titanate with a total mass of 50 ppm of sebacic acid and 3-methyl-1,5-pentanediol is added and mixed evenly, and the temperature is raised to 130°C to react until water is discharged; the temperature is then raised to 225°C, and the ester exchange reaction is carried out for 2 hours; the acid value of the material is then tested, and if the acid value is >25 mgKOH / g, the ester exchange reaction is continued for 10 minutes and the acid value is then tested again, and the above operation is repeated until the acid value is <25 mgKOH / g, and then the vacuum is evacuated to a gauge pressure from 0.018 MPa to 0.098 MPa, and the OH-value of the material is tested after 15 minutes. When the OH-value is 37.4±2, poly(3-methyl-1,5-pentanediol sebacic acid) ester with a number average molecular weight of 3000 is obtained.
[0105] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 26.2MPa, the tensile break rate (GB1040-79) is 967%, the tear strength (GB / T 529-2008) is 48.5kN / m, and the wear resistance is 38.8g / cm 2 .
[0106] The difference between Example 14 and Example 11 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 241.4g of 2,2-dihydroxymethylpropionic acid, 880g of polyadipate-3-methyl-1,5-pentanediol ester diol (Japan Kuraray P-2010), 1100g of low-crystalline dimer acid polyester polyol PLOS-ZY2250, 2000g of branched polytetrahydrofuran diol PTG-L-2000 (Japan Hotoko Chemical Industry Co., Ltd.), 440g of polycaprolactone hexamethylene carbonate diol CD2220PL (Japan Daicel Corporation), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0107] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 25.1MPa, the tensile break rate (GB1040-79) is 1027%, the tear strength (GB / T 529-2008) is 48.1kN / m, and the wear resistance is 40.2g / cm 2 .
[0108] The difference between Example 15 and Example 11 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 241.4g of 2,2-dihydroxymethylpropionic acid, 880g of poly-1,4-cyclohexanedicarboxylic acid-3-methyl-1,5-pentanediol ester diol (self-made by Zhejiang Hexin Technology Co., Ltd., molecular weight 2000), 968g of low-crystalline linear polyester polyol PLOS-ZY1200, 2100g of branched polytetrahydrofuran diol PTG-L-2000 (Japan Baotugu Chemical Industry Co., Ltd.), 440g of polycaprolactone hexamethylene carbonate diol CD2220PL (Japan Daicel Corporation), 3g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0109] The preparation method of poly 1,4-cyclohexanedicarboxylic acid-3-methyl 1,5-pentanediol ester diol is as follows: 1,4-cyclohexanedicarboxylic acid and 3-methyl 1,5-pentanediol are added into a reactor at a molar ratio of 2:2.1, and then sebacic acid and 80 ppm of 3-methyl 1,5-pentanediol tetraisopropyl titanate are added and mixed evenly, and the temperature is raised to 135°C to react until water is discharged; the temperature is then raised to 230°C, and the ester exchange reaction is carried out for 2 hours; and then the acid value of the material is tested If the acid value is >25 mgKOH / g, continue the ester exchange reaction for 10 min and then test the acid value. Repeat the above operation until the acid value is <25 mgKOH / g, then evacuate the vacuum until the gauge pressure is from 0.018 MPa to 0.098 MPa. After continuing for 15 min, test the OH value of the material. When the OH value is 56±3, the material is discharged to obtain poly (1,4-cyclohexanedicarboxylic acid-3-methyl-1,5-pentanediol) with a number average molecular weight of 2000.
[0110] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 25.5MPa, the tensile break rate (GB1040-79) is 972%, the tear strength (GB / T 529-2008) is 48.5kN / m, and the wear resistance is 39.5g / cm 2 .
[0111] The difference between Example 16 and Example 15 is that a low-hardness fast-molding TPU pellet for injection molding is composed of 111.2 g of isophorone diisocyanate IPDI, 210.3 g of Evonik TMDI 2,2,4-trimethylhexane diisocyanate, 875.9 g of MDI-50 (Covestro Desmodur 2460M), 118.2g of 3-methyl-1,5-pentanediol, 241.4g of 2,2-dihydroxymethylpropionic acid, 880g of poly-1,4-cyclohexanedicarboxylic acid-3-methyl-1,5-pentanediol ester diol (self-made by Zhejiang Hexin Technology Co., Ltd., molecular weight 2000), 968g of low-crystalline linear polyester polyol PLOS-ZY1200, 2100g of branched polytetrahydrofuran diol PTG-L-2000 (Japan Baotugu Chemical Industry Co., Ltd.), 440g of polycaprolactone hexamethylene carbonate diol CD2220PL (Japan Daicel Corporation), 20g of the solubilizing microcrystalline domain structuring agent in Preparation Example 1, 0.9g of dibutyltin dilaurate, 27g of antioxidant 1010, and 3g of antioxidant 168.
[0112] The Shore hardness (ASTM D 2240) of TPU pellets is 60A, the tensile strength (GB1040-79) is 32.6MPa, the tensile break rate (GB1040-79) is 905%, the tear strength (GB / T 529-2008) is 54.6 kN / m, and the wear resistance is 32.0g / cm 2 .
[0113] In summary, the hydroxyl group contained in the solubilizing microcrystalline region structuring agent reacts with the carboxyl group contained in 2,2-dihydroxymethylpropionic acid to produce an ester bond, and the solubilizing microcrystalline region structuring agent is connected to the TPU main chain as a side chain. The solubilizing microcrystalline region structuring agent serves as a physical cross-linking point, and the controllable design of the number of microcrystalline regions of the TPU as a whole can effectively improve the overall mechanical strength, wear resistance, heat resistance, and tear strength of the TPU. The solubilizing microcrystalline region structuring agent contains a phosphate group and an ester bond polar group, which can play a plasticizing and flame retardant role. The present invention realizes the addition of an appropriate amount of a solubilizing microcrystalline region structuring agent without affecting the overall hardness of the TPU, and enhances the overall mechanical strength, wear resistance, heat resistance, tear strength, and weather resistance, and prepares 58-65A low-hardness ultra-soft TPU pellets, filling the gap in low-hardness and high-performance TPU in China.
[0114] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A low-hardness fast-molding TPU pellet for injection molding, characterized in that: The low-hardness fast-molding TPU pellets for injection molding have a Shore hardness of 58-65A, an R value of 22-30wt%, a tensile strength of ≥20MPa, a tensile fracture rate of ≥1000%, a tear strength of ≥40 kN / m, and a wear resistance of <50g / cm 2 ; The low-hardness fast-forming injection molding TPU pellets are made of the following raw materials in parts by weight: 8-12 parts of aliphatic diisocyanate, 14-20 parts of aromatic diisocyanate, 4-8 parts of chain extender, 0.05-0.5 parts of solubilizing microcrystalline domain structuring agent, 68-72 parts of polyol, 0.00005-0.001 parts of catalyst, and 0.5-1 parts of antioxidant; The chain extender is composed of at least one of 2,2-dimethylol propionic acid, 2,2-dimethylol butyric acid, and N,N-dihydroxyethyl glycine and at least one of diol, diamine, and monoalcohol amine with a molecular weight of 60-500 g / mol; The preparation method of the solubilizing microcrystalline region structuring agent is as follows: surface activated carbon nanotubes are placed in a methacryloxysilane aqueous solution for ultrasonic dispersion treatment for 5-10 minutes, then reduced pressure filtration and vacuum drying are performed, the obtained surface grafted methacryloxy carbon nanotubes are dispersed in an organic solvent to obtain a carbon nanotube dispersion, hydroxy acrylate and an azo initiator are added to react at medium and low temperature for 5-30 minutes, reduced pressure filtration, multiple washings, vacuum drying, and ball milling to obtain a solubilizing microcrystalline region structuring agent; the hydroxy acrylate is at least one of di(hydroxyethyl) phosphate, 11-undecyl phosphonate, and rosin acid glycerol ester.
2. The low-hardness fast-molding TPU pellets for injection molding according to claim 1, characterized in that: The preparation method of the solubilizing microcrystalline domain structuring agent is as follows: S1. Place 0.5-2 parts of surface activated carbon nanotubes in 0.5-1L of a methacryloxysilane aqueous solution, wherein the surface activated carbon nanotubes are one or more of hydroxylated single-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, amino single-walled carbon nanotubes, and amino multi-walled carbon nanotubes, wherein the methacryloxysilane aqueous solution contains 0.05-0.5wt% methacryloxysilane, and the methacryloxysilane is at least one of KH 570 and KH 571, heat in a water bath to 40-45°C, perform ultrasonic dispersion treatment for 5-10 minutes, filter under reduced pressure, and dry under vacuum to obtain functional carbon nanotubes; S2. Disperse 0.5-2 parts of the functional carbon nanotubes with methacryloyloxy groups grafted on the surface of S1 in 200-500 mL of a toluene / DMF mixed solvent to obtain a carbon nanotube dispersion, and dropwise add a hydroxyacrylate / azo initiator mixture into the carbon nanotube dispersion, wherein the hydroxyacrylate is di(hydroxyethyl) phosphate, the azo initiator is azobisisobutyronitrile, the amount of the hydroxyacrylate / azo initiator mixture added is 0.01-0.2 times the mass of the functional carbon nanotubes, the mass ratio of hydroxyacrylate to azo initiator in the hydroxyacrylate / azo initiator mixture is 199:1, the dropping speed of the hydroxyacrylate / azo initiator mixture is 2-3 drops / min, heat in a water bath to 50-65°C, perform polymerization reaction for 10-15 minutes, cool to room temperature in an ice bath, perform reduced pressure filtration, rinse multiple times, vacuum dry, and ball mill to obtain a solubilizing microcrystalline domain framework agent.
3. The low-hardness fast-molding TPU pellets for injection molding according to claim 1, characterized in that: The aliphatic diisocyanate is at least one of isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hexamethylene-1,6-diisocyanate, and 2,2,4-trimethylhexamethylene diisocyanate; the aromatic diisocyanate is at least one of MDI, MDI-50, and carbodiimide-modified MDI.
4. The low-hardness fast-molding TPU pellets for injection molding according to claim 2, characterized in that: The aliphatic diisocyanate is isophorone diisocyanate and 2,2,4-trimethylhexamethylene diisocyanate; the aromatic diisocyanate is MDI-50; the mass ratio of isophorone diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate and aromatic diisocyanate MDI-50 in the aliphatic diisocyanate is (0.5-1):(1-2):(7-8).
5. A TPU pellet for low hardness fast molding injection molding according to claim 1, characterized in that: The catalyst is at least one of dibutyltin dilaurate, bismuth isooctanoate, and stannous octoate; the antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1035, antioxidant 1076, antioxidant 1098, and antioxidant 168.
6. The low-hardness fast-molding TPU pellets for injection molding according to claim 1, characterized in that: The diol in the chain extender is at least one of 1,5-pentanediol, 1,6-hexanediol, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, neopentyl glycol, diethylene glycol, and 3-methyl-1,5-pentanediol; the diamine in the chain extender is at least one of ethylenediamine, 1,6-hexanediamine, 1,4-butanediamine, and methylcyclohexanediamine; and the monoalcoholamine in the chain extender is ethanolamine and / or diglycolamine.
7. The low-hardness fast-molding TPU pellets for injection molding according to claim 1, characterized in that: The polyol is at least two of polyester diols, polyether diols, and polycarbonate diols with a number average molecular weight of 800 to 3500; the polyester diol is poly (3-methyl 1,5-pentanediol adipate), poly (3-methyl 1,5-pentanediol sebacate), poly (3-methyl 1,5-pentanediol 1,4-cyclohexanedicarboxylic acid), semi-crystalline dimer acid polyester polyol PLOS-ZY2100, low crystalline linear polyester polyol P The polyether diol is at least one of polytetramethylene glycol (PTMEG), branched polytetramethylene glycol (PTG-L), and branched polytetramethylene glycol (PTXG); the polycarbonate diol includes at least one of polycaprolactone hexamethylene carbonate diol and polycarbonate 3-methyl 1,5-pentanediol-1,6-hexanediol ester diol.
8. The low-hardness fast-molding TPU pellets for injection molding according to claim 6, characterized in that: The polyol has a number average molecular weight of 10 3 ~3*10 3 The polyester diol, polyether diol and polycarbonate diol are composed of a molar ratio of (20-40): (50-65): (5-20); the polyether diol is branched polytetrahydrofuran diol PTG-L-1000 and PTG-L-2000; the polycarbonate diol is a polytetrahydrofuran diol with a number average molecular weight of 10 3 ~2*10 3 Poly(hexamethylene carbonate) caprolactone glycol.
9. The low-hardness fast-forming TPU pellets for injection molding according to claim 8, characterized in that: The polyester diol is composed of poly 3-methyl 1,5-pentanediol sebacic acid ester diol and semi-crystalline dimer acid polyester polyol PLOS-ZY2100; or the polyester diol is composed of poly 3-methyl 1,5-pentanediol adipate diol and low-crystalline dimer acid polyester polyol PLOS-ZY2250; or the polyester diol is composed of poly 1,4-cyclohexanedicarboxylic acid-3-methyl 1,5-pentanediol ester diol and low-crystalline linear polyester polyol PLOS-ZY1200.
10. A method for preparing a low-hardness fast-forming injection molding TPU pellet according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, aliphatic diisocyanate, part of polyol, part of catalyst and part of antioxidant are uniformly mixed, and reacted at 90-95° C. for 80-120 min to obtain -NCO terminated polyurethane prepolymer A; The ratio of the molar amount of -NCO in the aliphatic diisocyanate to the molar amount of -OH in the polyol in the polyurethane prepolymer A is (1.05-1.5):1; the catalyst content in the polyurethane prepolymer A is 500-600ppm of the aliphatic diisocyanate; the added amount of the antioxidant in the polyurethane prepolymer A is 20-30wt% of the total weight of the antioxidant; Meanwhile, part of aromatic diisocyanate, part of polyol, part of catalyst and part of antioxidant are uniformly mixed, and reacted at 70-80° C. for 40-60 min to obtain -NCO terminated polyurethane prepolymer B; The aromatic diisocyanate in the polyurethane prepolymer B is 40-60wt% of the total mass of the aromatic diisocyanate; the ratio of the molar amount of -NCO in the aromatic diisocyanate polyol to the molar amount of -OH in the polyol in the polyurethane prepolymer B is (1.05-1.5):1; the catalyst content in the polyurethane prepolymer B is 150-300ppm of the aliphatic diisocyanate; the added amount of the antioxidant in the polyurethane prepolymer B is 30-40wt% of the total mass of the antioxidant; Step 2, adding the polyurethane prepolymer A in step 1 to the first trough of the twin-screw extruder; adding the polyurethane prepolymer B in step 1 to the second trough of the twin-screw extruder; stirring the accurately measured solubilizing microcrystalline region framework agent and the chain extender to obtain the mixture, and then stirring the remaining aromatic diisocyanate, chain extender, polyol, catalyst, and antioxidant at 60-65°C for 3-5 minutes to mix evenly, and then adding it to the third trough of the twin-screw extruder; the temperature of the first trough is 70-75°C, the temperature of the second trough is 60-65°C, the temperature of the third trough is 70-80°C, the extrusion temperature range of the twin-screw extruder is 160-220°C, and the twin-screw extruder is divided into twelve temperature zones, the setting temperature of the first temperature zone is 100-110°C, and the setting temperature of the second temperature zone is 200-300°C. The temperature is 120-125°C, the third temperature zone is set at 130-140°C, the fourth temperature zone is set at 150-160°C, the fifth temperature zone is set at 165-170°C, the sixth temperature zone is set at 180-185°C, the seventh temperature zone is set at 195-200°C, the eighth temperature zone is set at 195-200°C, the ninth temperature zone is set at 195-200°C, the tenth temperature zone is set at 180-185°C, the eleventh temperature zone is set at 160-165°C, the twelfth temperature zone is set at 145-150°C, the screw speed is 20-40rpm, the head temperature is 140-160°C, the screw aspect ratio is (40-48): 1, and a gear pump is used to discharge the material from the twin-screw extruder; Step three, the molten extrudate discharged from the twin-screw extruder in step two is water-cooled, granulated, and dried to obtain a semi-finished product, the semi-finished product is placed in a fluidized bed dryer, the temperature is adjusted to 80-85°C and dried for 8-12 minutes until the water content is less than 0.03%, and the obtained pellets are transferred to a 78-80°C oven for 20-24 hours of heat adjustment to obtain low-hardness fast-molding TPU pellets for injection molding.
Citation Information
Cited By
Antistatic sand-corrosion-resistant coating based on cyclodextrin modified carbon nanotube in-situ reinforced modification and preparation method of antistatic sand-corrosion-resistant coating
CN120795273A